Exogenous Arginine Treatment Maintains the Appearance and Nutraceutical Properties of Hard- and Soft-Seed Pomegranates in Cold Storage - Shi, Jiangli; Gao, Huifang; Wang, Sa; Wu, Wenjiang; Tong, Ruiran; Wang, Sen; Li, Ming; Jian, Zaihai; Wan, Ran; Hu, Qingxia; Zheng, Xianbo; Chen, Yanhui (Frontiers in Nutrition, 2022)
Arginine is a natural preservative; however, its effects on the storage of different cultivars of pomegranates have not been investigated extensively. Therefore, the fruit quality of soft-seed Tunisia and hard-seed Yudazi pomegranates was investigated after treatment with arginine at four concentrations during cold storage for 80 d. Pomegranates treated with 1.0 mM arginine exhibited a relatively lower loss of vitamin C, soluble solid, total phenol, and anthocyanin contents in arils, together with a better fruit appearance. Combined with principal component analysis, the storage life of fruits treated with 1.0 mM arginine showed a higher correlation with antioxidant enzyme activity (including superoxide dismutase, ascorbate peroxidase, and catalase) during the first 40 d of cold storage, whereas after 40 d of cold storage, storage life was more dependent on the integrity of the cell membrane affected by malondialdehyde content, electrolyte leakage, and H2O2 accumulation. Arginine treatment contributed significantly to the appearance and inner quality of the hard-seed pomegranate cv. Yudazi fruit during cold storage compared to those of soft-seed Tunisia. Taken together, arginine application combined with cold storage enhanced the nutraceutical properties and marketability of pomegranate fruits.